Optimizing the Role of Waqf in the Development of Halal Tourism in Indonesia - Nizar, Muhammad; Antin Rakhmawati; Bahjatis Sania (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2025)
Purpose: The purpose of this study is to analyze and understand the role of waqf as an alternative source of funding in the development of halal tourism in Indonesia. Methodology: This research adopts a literature study approach by collecting, analyzing, and synthesizing data from various relevant sources to draw comprehensive conclusions. Findings: The study finds that the significant potential of waqf funds in Indonesia can be optimized as an alternative financing mechanism for halal tourism development projects. This potential is supported by Indonesia’s status as the country with the largest Muslim population, its strategic geographical location, rich biodiversity, and extensive natural landscapes. Utilizing waqf funds can enhance productivity and ensure better management outcomes for the benefit of the ummah. Furthermore, this financing alternative supports the circulation of the halal value chain within the halal tourism supply chain in Indonesia. Research limitations: This study is based on a literature review; thus, future empirical research is needed to validate the practical application of waqf-based financing models in halal tourism projects. Practical implications: The findings provide insights for policymakers, investors, and tourism developers on the potential of integrating waqf-based funding to strengthen the halal tourism sector. Social implications: Implementing waqf funds in halal tourism development can contribute to broader social welfare, promote economic inclusivity, and enhance community empowerment aligned with Islamic economic principles. Originality: This study highlights the underexplored potential of waqf as an innovative and sustainable financing solution for the development of halal tourism in Indonesia. Keywords: Waqf; Halal Tourism; Indonesia; Islamic Economics; Tourism Development